Trend in the incidence of type 1 diabetes (T1DM) among Qatari and Arab gulf children and adolescents over the past 20 years - Soliman, Ashraf T; De Sanctis, Vincenzo; Alaaraj, Nada; Alyafei, Fawzia; Hamed, Noor; Ahmed, Shayma (Acta Biomedica Atenei Parmensis, 2022)
Letter to Editor